Case Report: Pneumomediastinum and pulmonary embolism in a 19-year-old with focal segmental glomerulosclerosis: a rare double-complication of corticosteroid therapy - Rotaru, Demetra Emanuela; Achim, Alexandru (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFocal Segmental Glomerulosclerosis (FSGS) is a common aetiology of nephrotic syndrome and a leading cause of end-stage renal disease. Corticosteroid therapy is considered the first-line treatment in patients with proteinuria, but it carries a heterogeneous range of common and rare complications.Case summaryWe report the case of a 19-year-old patient, recently diagnosed with FSGS secondary to anabolic steroid use and receiving glucocorticoid therapy, who presented to our emergency department with acute respiratory distress and neck swelling. He was subsequently diagnosed with pneumomediastinum and acute bilateral saddle pulmonary embolism (PE).DiscussionThe rare occurrence of FSGS treated with glucocorticoid therapy, complicated by severe thromboembolic events and pneumomediastinum, emphasizes the complexity of managing the treatment of a young patient by balancing the risks and benefits and tailoring the dosage to achieve maximal therapeutic effect with minimal adverse events.ConclusionClose monitoring should be provided to patients with a procoagulant status due to nephrotic syndrome, as well as to those at additional risk from corticosteroid treatment.